THE STRATEGIC ROLE OF ENVIRONMENTAL ACCOUNTING IN PROMOTING BUSINESS SUSTAINABILITY IN INDONESIA - agustina, ika; Rahmanu, Ichwan; Saputri, Haria; Tahang, Moh (JURNAL ASIK, 2024)
Environmental accounting is increasingly recognized as an important strategic instrument for organizations faced with sustainability challenges. This article investigates the utilization of environmental accounting in Indonesian companies, with a particular emphasis on how this practice can improve transparency, operational efficiency, and corporate reputation. Using document analysis methodology, the research examined related reports on sustainability, environmental policies, and government regulations. The results showed that companies implementing environmental accounting successfully achieved reductions in carbon emissions and waste, in addition to improving energy efficiency. In addition, the adoption of environmental accounting resulted in substantial financial benefits, including reduced operating expenditures. Nonetheless, barriers such as initial investment requirements and regulatory intricacies continue to pose challenges for many companies. Consequently, collaboration between government entities, private companies, and non-governmental organizations is essential to promote wider adoption of environmental accounting practices. This study sheds light on the importance of environmental accounting in fostering a more sustainable future for Indonesia.